Representing Islam in Indonesian Film Advertising during the Suharto Era (1966–1998) and Reform Era (1998–Present) - Woodrich, Christopher A. (Universitas Muhammadiyah Yogyakarta, 2018)
This article examines how Islam has been depicted in advertisements for Indonesian films over the past fifty years. It finds that, during the Suharto Era (1966–1998), Islam was generally not represented explicitly in film advertisements; however, examples could still be found in advertisements for films intended to preach Islamic values as well as in advertisements for films with more general themes. The use of Islamic symbols became more common during the Reform Era (1998–present), particularly following the rise of the film Islami genre. Advertisements in both eras used such symbols as turbans, skullcaps, and headscarves, as well as other common symbols of Islam. However, advertisements differed in two key aspects. First, where advertisements in the Suharto era tended to embrace viewers of all backgrounds, advertisements in the Reform era have often positioned Islam as more exclusive. Second, where advertisements in the Suharto era tended to illustrate a dynamicity in discourses on Islamic identity, advertisements in the Reform era have generally promoted a more singular understanding of Indonesian Islamic identity.